1996
DOI: 10.1037/0021-9010.81.4.443
|View full text |Cite
|
Sign up to set email alerts
|

A 20-year stability analysis of the study of values for intellectually gifted individuals from adolescence to adulthood.

Abstract: A sample of 203 intellectually gifted adolescents (top 1%) were administered the Allport-Vernon-Lindzey (1970) Study of Values (SOV) at age 13; 20 years later, they were administered the SOV again. In this study, researchers evaluated the intra-and interindividual temporal stability of the 6 SOV themes, namely, Theoretical (T), Economic (E), Political (P), Aesthetic (A), Social (S), and Religious (R). Over the 20-year test-retest interval, the SOWs mean and median interindividual correlations for the 6 themes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 39 publications
(66 reference statements)
5
67
0
Order By: Relevance
“…Each generation is influenced by broad forces (i.e., parents, peers, media, critical economic and social events, and popular culture) that create common value systems distinguishing them from people who grew up at different times. These forces are strongest during an individual's childhood and adolescence; for example, work values remain relatively stable from early adolescence to young adulthood (Lubinski, Schmidt, & Benbow, 1996;Meglino & Ravlin, 1998). According to Scott (2000, p. 356), this value system or view of the world "stays with the individual throughout their lives and is the anchor against which later experiences are interpreted.…”
Section: Generation Cohortsmentioning
confidence: 99%
“…Each generation is influenced by broad forces (i.e., parents, peers, media, critical economic and social events, and popular culture) that create common value systems distinguishing them from people who grew up at different times. These forces are strongest during an individual's childhood and adolescence; for example, work values remain relatively stable from early adolescence to young adulthood (Lubinski, Schmidt, & Benbow, 1996;Meglino & Ravlin, 1998). According to Scott (2000, p. 356), this value system or view of the world "stays with the individual throughout their lives and is the anchor against which later experiences are interpreted.…”
Section: Generation Cohortsmentioning
confidence: 99%
“…As stated above, the years included are clustered into four sub-periods: 1979(I), 1987(II), 1994-1996(III), and 2001-2003. The fact that the ULF comprises a rich set of information and covers a relatively long time span offers unique possibilities for analysing long-term trends, in this case changes in the distribution of attitudes to work.…”
Section: Data Included Variables and Methodsmentioning
confidence: 99%
“…Understood in this way, they represent standards of behaviour towards which the individual has a strong positive attitude (Liu & Lay, 2012). Different generations face different experiences and events during their lives, and this might, in turn, generate different experiences, expectations and values about work that are then expressed as generational differences of attitude (Cennamo & Gardner, 2008;Lubinski, Schmidt, & Benbow, 1996;Meglino & Ravlin, 1998). In a recent study from the United States, Twenge et al (2010) compared work values of three different generations born after World War II and found that leisure values (i.e., extrinsic values) increased steadily over the generations, while work centrality and emphasis on intrinsic work values declined.…”
Section: Theoretical Framework and Earlier Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In understanding values, Spranger (1928) (Hechter, 1993). After the 1980s, interest in personal values studies became more diverse, with the stability of personal values (e.g., Lubinski, Schmidt, & Benbow, 1996;Rokeach & Ball-Rokeach, 1989), methodological advancement (England & Lee, 1974;Maznevski, Gomez, DiStefano, Noorderhaven, & Wu, 2002) and many other aspects being investigated. Among a number of researchers, Schwartz (1992Schwartz ( , 1994b) is recognised as the most widely known scholar in the recent study of personal values (Krystallis & Vassallo, 2012;Ralston et al, 2011).…”
Section: Key Studies In Personal Valuesmentioning
confidence: 99%